2017
DOI: 10.1140/epjc/s10052-017-4725-9
|View full text |Cite
|
Sign up to set email alerts
|

EPPS16: nuclear parton distributions with LHC data

Abstract: We introduce a global analysis of collinearly factorized nuclear parton distribution functions (PDFs) including, for the first time, data constraints from LHC proton–lead collisions. In comparison to our previous analysis, EPS09, where data only from charged-lepton–nucleus deep inelastic scattering (DIS), Drell–Yan (DY) dilepton production in proton–nucleus collisions and inclusive pion production in deuteron–nucleus collisions were the input, we now increase the variety of data constraints to cover also neutr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
737
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 595 publications
(790 citation statements)
references
References 110 publications
38
737
2
3
Order By: Relevance
“…(Color online) The CMS dijet measurements 78 are compared to NLO theory calculations. 81 The predictions employ the CT10 free proton PDFs 54 (purple dashed curve) and the CT10 PDFs modified by the EPS09 NLO 55 nuclear modifications (blue curve). The upper panel shows the normalized cross section as a function of η dijet .…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…(Color online) The CMS dijet measurements 78 are compared to NLO theory calculations. 81 The predictions employ the CT10 free proton PDFs 54 (purple dashed curve) and the CT10 PDFs modified by the EPS09 NLO 55 nuclear modifications (blue curve). The upper panel shows the normalized cross section as a function of η dijet .…”
Section: 2mentioning
confidence: 99%
“…In this measurement, the jets were binned in dijet pseudorapidity, η dijet , defined as the average pseudorapidity of the two hardest (largest p T ) jets in the event, η dijet ≡ 0.5(η leading + η subleading ) (in the laboratory frame). The momentum fractions probed on the nucleus side is approximately x 2 ≈ (2p [81], such that the η dijet dependence rather straightforwardly tracks the x dependence of the nuclear PDFs.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In particular, very little is known about the gluon PDF in nuclei, which is, however, important to understand nuclear shadowing [8] and its possible relation to diffraction [9], saturation [10], and the initial condition for the creation of the quark-gluon plasma in heavy-ion collisions [11]. The situation could be somewhat improved by including pion production data from BNL RHIC [12], albeit at the cost of introducing a fragmentation function uncertainty, and recently also with the first electroweak boson [13] and in particular dijet [14] data from pPb collisions at the CERN LHC [15]. In addition, a recent reweighting study has shown also that forward heavy-quark and quarkonium production data from the CERN LHC have the potential to better constrain future analyses [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is based on proton PDFs similar to CTEQ6.1 [56], but with minimal influence from nuclear data. For comparison, we will also show nCTEQ15 estimates with additional constraints from inclusive pion data taken by the PHENIX and STAR experiments at RHIC as well as estimates with the latest EPPS16 nuclear PDF fit [57] that already includes LHC data from ATLAS and CMS on electroweak gauge boson and dijet production in pPb collisions. The nCTEQ and EPPS16 fits come with 32 and 40 error PDFs, respectively, which we will show as shaded bands.…”
Section: Jhep03(2018)081mentioning
confidence: 99%